Fetal atrial appendage aneurysm: Prenatal diagnosis by echocardiography and prognosis. Issue 8 (1st June 2021) - Wang, Xin; Liu, Jing‐jing; Han, Jian‐cheng; Sun, Lin; Zhang, Ye; Gu, Xiao‐yan; Xue, Chao; Liu, Xiao‐wei; He, Yi‐hua
Abstract: Background: Congenital atrial appendage aneurysm (AAA) is a rare malformation which can coexist with potentially lethal complications. We aimed to summary echocardiographic characteristics and prognosis of fetal AAA. Methods: We retrospectively analyzed the echocardiographic data of 17 fetuses with AAA，and their outcomes or pathological reports were also collected. Results: Eight fetuses with left AAA (LAAA) and 9 fetuses with right AAA (RAAA) were identified. Five fetuses were diagnosed with other cardiac defects. Two fetuses with RAAA presented with arrhythmias, including atrial premature beats (n = 1) and bradyarrhythmia (n = 1). LAAA could be detected by four‐chamber view (50.0%) and short‐axis view (100.0%). RAAA could be detected by four‐chamber view (100.0%), and view of right ventricular inflow tract (33.3%). There were three cases with mild pericardial effusion. Three cases with complex cardiac defects were selectively terminated, with confirmation of LAAA by autopsy in one case. Fourteen fetuses were born. After following 2 (range, 1–5) years, the AAA disappeared in one case with LAAA and two cases with RAAA. While, 11 cases were still diagnosed with AAA. Atrial premature beats with RAAA, which appeared in prenatal period, still persisted after birth. Conclusion: Congenital AAA is a rare abnormality in utero. The short‐axis view and the four‐chamber view were the most useful views to detect fetal AAA. Fetal AAA may disappear in childhood. Atrial tachyarrhythmias in utero may exist persistently after birth. Patients with AAA should be followed up closely and appropriate intervention should be taken when complications appeared.